Pengembangan Sistem Informasi Manajemen Inventory Berbasis Website pada Minimarket Sixteen - David Saputra Octadianto Soedargo; Titasari Rahmawati (J-INTECH ( Journal of Information and Technology), 2024)
The digital era requires all businesses to shift from traditional industries to industries that utilize information technology. One of the businesses affected is a minimarket, which is a type of business that combines the concept of self-service on a small scale with a target market in line with traditional markets. Sixteen minimarket is an individual business managed by a food retail company and various kinds of daily necessities. The entire process of bookkeeping at Sixteen minimarkets is still done manually. This can lead to the risk of human error in producing goods reports and stock information. Manual bookkeeping can also be at risk of being lost or damaged. Apart from that, the data search process can also take quite a long time. This results in less than optimal service. A website-based inventory management information system was developed to solve this problem. The development method used is Waterfall. The design process includes the design of the Entity Relationship Diagram (ERD), Conceptual Data Model (CDM), and Physical Data Model (PDM). This information system can record goods reports and stock information more quickly, efficiently and accurately. Apart from that, it can also minimize the risk of human error.